A Case of Heterochronic Development of Extrahepatic Bile Duct Carcinoma and Cholangiocellular Carcinoma - Katoh, Hiroyuki; Kondo, Satoshi; Okushiba, Shunichi; Omi, Makoto; Shimizu, Michio; Nakakubo, Yoshihiro; Ambo, Yosiyasu; Hirano, Satoshi; Morikawa, Toshiaki (Nippon Shokaki Geka Gakkai zasshi, 2001)
We report a rare case of heterochronic development of extrahepatic bile duct carcinoma and cholangiocellular carcinoma. A 49-year-old woman was diagnosed with middle and lower bile duct carcinoma and pancreati-coduodenectomy and Whipple's reconstruction were conducted in June 1994. Four years later, the woman was admitted to our hospital suffering from diarrhea. Abdominal computed tomography (CT) and cholangiography revealed a liver tumor. We suspected recurrence of bile ductcarcinoma in the PTBD fistula in the liver, and conducted extended left and caudate lobectomy and resectioning of the choledochojejunostomy. Histopathologically, the tumor was diagnosed as cholangiocelluar carcinoma, and clarified to be heterochronic double cancer.